2017
DOI: 10.1111/1467-8268.12275
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of China's and Japan's Foreign Aid Allocations in Africa

Abstract: Foreign aid plays an important role in promoting economic development in Africa. Recently, several countries, most notably China, have emerged as alternative sources of foreign aid. However, their motives for providing foreign aid have been questioned. The present study examines and compares determinants of China's and Japan's foreign aid allocations in Africa. It assumes that the distribution of foreign aid was determined by the aid donors' self-interest and also by the aid recipients' needs. Three panel mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…In fact, only 12 out of 21 agricultural projects are unfunded compared to infrastructures (see Table 2). Third, this outcome may support Furuoka (2017) that Chinaʼs provision of foreign aid is mostly driven by its self-interest.…”
Section: Causality Test Resultsmentioning
confidence: 75%
“…In fact, only 12 out of 21 agricultural projects are unfunded compared to infrastructures (see Table 2). Third, this outcome may support Furuoka (2017) that Chinaʼs provision of foreign aid is mostly driven by its self-interest.…”
Section: Causality Test Resultsmentioning
confidence: 75%
“…Despite this need, there is almost no empirical analysis. While several studies have attempted to analyze China, Japan, and Korea individually for each country's motives behind foreign aid allocations (Cooray and Shahiduzzaman 2004;Fuchs and Rudyak 2019;Park & Lee 2015), only a few studies have conducted comparative analyses of Japan and China (Furuoka 2017) or Japan and Korea (Kang et al 2011). Yet, it is challenging to find a comprehensive comparative analysis of these three countries of their behaviors related to foreign aid.…”
Section: An East Asian Model Of Foreign Aidmentioning
confidence: 99%
“…The analysis of the relationship between foreign aid on economic development is complicated by potential endogeneity of aid as donors tend to allocate foreign aid to countries and areas within countries that have a track record of demonstrated capacity to manage and absorb it efficiently (Furuoka, 2017; Wilson, 2011). To account for the endogeneity problem, previous studies have used lagged aid as an instrument for current aid and yet found mixed results regarding the effect of aggregate aid or sector‐specific aid on infant or child mortality (Boone, 1996; Masud & Yontcheva, 2005; Mary & Gomez y Paloma, 2015; Pickbourn & Ndikumana, 2019).…”
Section: Introductionmentioning
confidence: 99%